Dan in real life - Shestack, Jonathan; Epstein, Brad.; Gardner, Pierce; Hedges, Peter; Carell, Steve, 1963-; Binoche, Juliette, 1964-; Cook, Dane.; Mahoney, John, 1940-; Blunt, Emily; Wiest, Dianne; Touchstone Pictures; Focus Features; et al. (Burbank, CA : Distributed by Buena Vista Home Entertainment, Distributed by Buena Vista Home Entertainment, 2008)
Dan Burns is a local newspaper advice columnist. He is a widower with three daughters. He brings the family to his parent's house for a family gathering. When Dan goes to a local bookstore, he meets Marie. When he gets home, he finds out that Marie is actually dating his brother Mitch. Dan's mother Nana announces that she met an old acquaintance of Dan's, Ruthie Draper and that she has set up a date between Dan and Ruthie. Dan refuses to go. Mitch suggests that they could make it a double date and Dan agrees. Ruthie turns out to be very hot, but Dan isn't really interested in her. When Marie indicates that Ruthie is not right for him, Dan feigns interest and starts dancing with Ruthie. Marie gets jealous and joins the floor with Mitch, leading to an upstaging contest between Dan and Marie.
Region 1, widescreen (1.85:1, enhanced) presentation; Dolby Digital 5.1 surround, digitally mastered.
Originally released as a motion picture in 2007.
Special features: Deleted scenes with commentary by writer/director Peter Hedges; real-life outtakes; "Just like family: the making of Dan in real life" featurette; "Handmade music: creating the score" featurette; audio commentary with writer/director Peter Hedges.
Director of photography, Lawrence Sher ; editor, Sarah Flack ; music, Sondre Lerche ; costume designer, Alix Friedberg ; production designer, Sarah Knowles ; produced by Jon Shestack, Brad Epstein ; written by Pierce Gardner and Peter Hedges ; directed by Peter Hedges.
Steve Carell, Juliette Binoche, Dane Cook, John Mahoney, Emily Blunt, Dianne Wiest.
MPAA rating: PG-13; for some innuendo.
Keywords: Widowers -- Drama. -- United States; Man-woman relationships -- Drama. -- United States; Dating (Social customs) -- Drama. -- United States; Fathers and daughters -- Drama. -- United States; Brothers -- Drama. -- United States; Mothers and sons -- Drama. -- United States; Feature films; Romantic comedy films; Video recordings for the hearing impaired; Romance -- Feature; Comedy -- Feature; Family -- Feature; Feature films; Comedy films